Biosorption processes for heavy metal removal - Saini, Pinki (IGI Global, 2024)
Persistent and non-degradable, heavy metals stand as pollutants with the potential for severe ecological repercussions when released into the environment. Municipal and industrial wastewater face a high risk of contamination by these hazardous substances, posing a formidable challenge to water treatment technologies. The imperative is clear: effective and affordable methods for effluent treatment and metal recovery are essential for meeting regulatory standards and unlocking the latent value of valuable metals within the waste. However, new methods of accomplishing this challenge are necessary for increasing the effectiveness in both cost and applicationBiosorption Processes for Heavy Metal Removal comprehensively explores the imperative to remove heavy metals from waste streams. It provides an insightful overview of biosorbents and biosorption technology, focusing on their underlying biosorption features. The compilation within this book comprises of a series of review articles delving into the current understanding of biosorption mechanisms and biochemistry, the efficacy of bacterial, fungal, and algal biomass, and practical considerations for biosorbent preparation and engineering. The physicochemical evaluations of biosorbents, process optimization, and factors influencing biosorption efficiency are also covered. Furthermore, the book explores biosorption applications for removing nutrients, organic pollutants, and metals in wastewater treatment across diverse contexts. Geared towards administrators, policymakers, consultants, industry professionals, academicians, scientists, researchers, and graduate and post-graduate students in environmental sciences and related fields, this book serves as their comprehensive reference.
Keywords: Bioremediation; Heavy metals -- Environmental aspects